A framework to interpret co‐occurrence patterns from camera trap data: The case of the gray fox, the bobcat, and the eastern cottontail rabbit in a tropical dry habitat. (20th August 2022) - Andrade‐Ponce, Gabriel Patricio; Mandujano, Salvador; Dáttilo, Wesley; Farías‐González, Verónica; Jiménez, José; Velásquez‐C, Karen; Zavaleta, Arturo
Abstract: In mammals, ecological interactions are difficult to observe directly, so they are usually inferred from co‐occurrence data. Direct interpretation of co‐occurrence patterns can be complicated since they may be the result of different processes such as habitat selection. We propose a logical framework along with multispecies occupancy models, to distinguish which process or interaction of processes gives rise to co‐occurrence patterns. We also used temporal kernel density estimates to explore the overlap in diel activity patterns, and ecological knowledge of the species as a complement to explain the drivers that generate co‐occurrence. To test our framework, we analyzed three mammal species: the bobcat ( Lynx rufus ), the gray fox ( Urocyon cinereoargenteus ), and their potential prey, the eastern cottontail rabbit ( Sylvilagus floridanus ), in a tropical dry habitat at Tehuacán‐Cuicatlán Biosphere Reserve, Mexico. Data were collected across 67 camera trap stations that operated from February to August 2018. The best‐fitted model described the spatial interaction between U. cinereoargenteus and L. rufus with S. floridanus ; in both cases, the occupancy probability of the predatory species was higher in the presence of their prey than in their absence. Additionally, the three species presented a high overlap in their temporal activity patterns. Based on the knowledge of the species' ecology and our results, we identified that trophic interactions could be an important process shaping the co‐occurrence patterns of these species. In short, our framework highlights that it is possible to discern among the processes that influence the co‐occurrence patterns for species with well‐defined ecological roles, such as in our study system. Abstract : We propose a framework for interpreting spatial co‐occurrence patterns from camera trap data. The framework compares different processes such as ecological interactions and habitat filters, including temporal activity patterns and prior ecological knowledge of the species. Ecological interactions were the primary mechanism shaping bobcat, gray fox, and cottontail rabbit co‐occurrence patterns. Resumen: En el caso de los mamíferos, las interacciones ecológicas son difíciles de observar directamente, por lo que suelen inferirse a partir de los datos de co‐ocurrencia. La interpretación directa de los patrones de co‐ocurrencia es complicada, puesto que éstos pueden ser el resultado de diferentes procesos, como la selección de hábitat. Utilizamos un marco lógico junto con modelos de ocupación multi‐especie, para distinguir que proceso o interacción de procesos da lugar a los patrones de co‐ocurrencia. También utilizamos estimaciones de densidad de kernel temporal para explorar el solapamiento de los patrones de actividad diarios, y el conocimiento ecológico de las especies como complemento para explicar los procesos que generan los patrones de co‐ocurrencia. Para probar nuestro marco, analizamos tres especies de mamíferos: El gato montés ( Lynx rufus ), la zorra gris ( Urocyon cinereoargenteus ), y su presa potencial el conejo cola de algodón ( Sylvilagus floridanus ) en un hábitat tropical seco en la Reserva de la Biosfera Tehuacán‐ Cuicatlán, México. Los datos fueron recolectados a través de 67 estaciones de cámaras trampa que operaron de febrero a agosto de 2018. El modelo mejor ajustado describió la interacción espacial entre U. cinereoargenteus y L. rufus con S. floridanus, en ambos casos la probabilidad de ocupación de las especies depredadoras fue mayor en presencia de su presa. Adicionalmente, las tres especies presentaron solapamiento en sus patrones de actividad. Basándonos en el conocimiento de la ecología de las especies y en nuestros resultados, identificamos que las interacciones tróficas fueron el principal proceso que explica los patrones de co‐ocurrencia de estas especies. Nuestro marco resalta que es posible discernir entre los procesos que influyen en los patrones de co‐ocurrencia para especies con roles ecológicos definidos, como en nuestro sistema de estudio.